PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN BIOLOGI - Ni Kadek Dewi Novianti; Handoko Santoso; Agil Lepiyanto (Bioedukasi Jurnal Pendidikan Biologi, 2020)
The Effect of using the Problem Based Instruction (PBI) learning model to determine the effect on learning outcomes using the Problem Based Instruction (PBI) learning process. This research is a quasi experimental research which consists of a control class and an experimental class. The control class uses the conventional learning model and the experimental class uses the Problem Based Instruction (PBI) learning model, conducted in the X MIPA 1 and X MIPA 2 in SMA Negeri 1 Rumbia. The research data were obtained from test sheets and observations at the end of each lesson. The average cognitive learning outcomes of the experimental class were 80% and the control class was 63,83%. The average psychomotor learning outcomes of the experimental class were 80,46% and the experimental class was 75%. The results showed that there was an influence of the Problem Based Instruction (PBI) learning model on the learning outcomes of students in learning biology. Kata Kunci : Model Pembelajaran Problem Based Instruction (PBI), Hasil, Belajar peserta didik